2009
DOI: 10.1002/hbm.20725
|View full text |Cite
|
Sign up to set email alerts
|

A multiparametric evaluation of regional brain damage in patients with primary progressive multiple sclerosis

Abstract: The purpose of this study is to define the topographical distribution of gray matter (GM) and white matter (WM) damage in patients with primary progressive multiple sclerosis (PPMS), using a multiparametric MR-based approach. Using a 3 Tesla scanner, dual-echo, 3D fast-field echo (FFE), and diffusion tensor (DT) MRI scans were acquired from 18 PPMS patients and 17 matched healthy volunteers. An optimized voxel-based (VB) analysis was used to investigate the patterns of regional GM density changes and to quanti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
35
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 43 publications
(39 citation statements)
references
References 50 publications
3
35
1
Order By: Relevance
“…Similar to our findings, an increased thalamic MD in patients with MS with different clinical disease phenotypes in comparison with healthy controls was found in these studies, on average. 9,16,17,31 However, contrary to our results, an increased thalamic FA has been described. 17,31 Several factors might contribute to explaining the discrepancy between ours and previous findings concerning baseline thalamic FA abnormalities, including the fact that previous studies recruited patients with different MS phenotypes, predominantly relapsing-onset MS, whereas we enrolled patients with PPMS only.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Similar to our findings, an increased thalamic MD in patients with MS with different clinical disease phenotypes in comparison with healthy controls was found in these studies, on average. 9,16,17,31 However, contrary to our results, an increased thalamic FA has been described. 17,31 Several factors might contribute to explaining the discrepancy between ours and previous findings concerning baseline thalamic FA abnormalities, including the fact that previous studies recruited patients with different MS phenotypes, predominantly relapsing-onset MS, whereas we enrolled patients with PPMS only.…”
Section: Discussioncontrasting
confidence: 99%
“…Previous studies in patients with early PPMS (within 5 years of symptom onset) have reported that thalamic atrophy 9,23,30 and thalamic microscopic damage, quantified by using magnetization transfer imaging 30 and DTI, 9 are early features of PPMS. However, little is known about the temporal pattern of the evolution of these abnormalities and their relationship with disability accumulation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, deep GM nuclei are site of relevant atrophy as well, i.e., compared to matched healthy subjects, up to 25% loss of the thalamus volume has been demonstrated in RRMS [24][25][26][27][28]. GM atrophy becomes more widespread and severe in secondary (SPMS) and primary progressive MS (PPMS) [29][30][31][32][33][34][35][36][37] and, in some patients, may undertake a dramatic acceleration, i.e., up to 14-fold compared to age-matched healthy individual [16,36]. Although PPMS and SPMS show similar extent of total GM atrophy, different regional atrophy distribution was described in these two types of MS [34][35][36][37] and some correlations between regional WM lesion load and GM atrophy were more often observed in SPMS compared to PPMS, a finding somehow expected given the differences in the WM lesion load that characterize these two MS types.…”
Section: Introductionmentioning
confidence: 99%
“…64 With a voxel-based approach, a significant correlation was found in PPMS between a regional decrease of MTR values of cortical areas of the motor network and the EDSS scores as well as between MTR values in cortical areas of the cognitive network and the Paced Auditory Serial Addition Test scores. 65 Ceccarelli et al 66 showed DTI abnormalities in brain areas associated with motor and cognitive functions in PPMS (Fig 3). Bodini et al 67 found 11 brain regions with an anatomic corre- spondence between reduced NAWM FA values and GM atrophy in patients with early PPMS.…”
mentioning
confidence: 96%